Narratives of war
1 online resource.
Keywords: "Narratives of War considers the way war and battle are remembered and narrated across space and time in Europe in the twentieth century. The book reflects on how narratives are generated and deployed, and their function as coping mechanisms, means of survival, commemorative gestures, historical records, and evidence with reference to a variety of wars and narratives genres. Approached from a multidisciplinary perspective, and taken together, analysis of these narratives contributes to our understanding of the causes, experience, dynamics, and consequences of war, making it the ideal book for those interested in twentieth-century military history and memory and history"--